Model Desentralisasi Program Makan Bergizi Gratis (MBG) Berbasis Sekolah: Memangkas Rantai Pasok dan Mencegah Penyelewengan - Cahyo Wibowo; Muhammad Muryanto; Saeful Rofi Romadhon (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
The Free Nutritious Meals Program (MBG), launched in January 2025, is one of the national priority programs with a budget of Rp223 trillion in 2026. However, its centralized implementation through the Nutrition Fulfilment Service Units (SPPG) faces various serious systemic problems. By the end of 2025, there were more than 20,000 reported cases of food poisoning, two fatalities, as well as chronic distribution delays, substandard nutritional quality, targeting inaccuracies, and corrupt practices involving non-essential actors. This article aims to formulate a school-based MBG decentralization model with three main pillars: (1) the phased elimination of all SPPGs, (2) the direct disbursement of funds from the National Nutrition Agency (BGN) to schools without intermediaries, and (3) a ban on the involvement of non-essential institutions in the distribution chain. The methods used include a projected case study with comparative policy analysis and a systematic literature review of 30 indexed journals from the past 10 years. The proposed model channels funds directly from the BGN to school accounts; preparation, cooking, and distribution are carried out on school premises with the rotating involvement of parents; raw material suppliers are selected from local farmers/vendors through a rotation system; monitoring is conducted by both the school committee and parents; and meal portions are adjusted according to the actual number of students present. This model recommends the phased discontinuation of the SPPG over a 6-month period, as well as the closure of the entire distribution chain involving non-essential actors. The main recommendation is a limited pilot program in 20–30 non-urban schools as the basis for reforming the national MBG governance system